Balance sheet effects in Colombian non-financial firms - Adolfo Barajas; Sergio Iván Restrepo Ochoa; Roberto Steiner; Juan Camilo Medellín; César Pabón (Inter-American Development Bank (IDB), 2016)
After building up foreign currency-denominated (FC) liabilities over several years, the balance sheets of Colombian firms might be particularly vulnerable to a shift in external conditions. This paper undertakes four exercises in order to get a better understanding of these vulnerabilities. First, probit/logit estimations are used to identify the firm-level and macroeconomic determinants of FC borrowing by non-financial corporations. Second, the implications of the balance sheet vulnerability for real activity are investigated. Evidence is found of an FC balance sheet effect that transmits exchange rate fluctuations to firm-level investment, and show that that this effect is asymmetric, much greater for depreciations than for appreciations. Third, using logit/probit estimations, it is shown that not all firms use forward exchange derivatives solely to hedge their FC liabilities. This might be a consequence of exchange rate intervention by the monetary authority, protecting against extreme exchange rate misalignments. Finally, results are reported of a survey-based qualitative analysis on the hedging policies and activities of 12 large non-financial firms.
hdl:11319/7936
Keywords: E22; F31; 330; Colombia; Depreciation; Dollar debt; Balance sheet effects